Scottish Art in the Industrial Age, 1800-1914.
1 online resource
Keywords: This volume examines the emergence of a market for Scottish art among Scotland's wealthy industrialists in the mid-nineteenth century and in the period leading up to the First World War. As well as considering key mercantile collectors such as James Guthrie Orchar and James Keiller in Dundee, James Duncan in Greenock, John Forbes White in Aberdeen and Sir William Burrell and William McInnes in Glasgow, it focuses on major art dealers such as Alexander Reid, who gave the artists Joseph Crawhall, George Henry and E.A. Hornel their first solo exhibitions. In Edinburgh Scottish artists were supported initially by Alexander Hill and later by Peter McOmish Dott at the Scottish Gallery, who supported the Scottish Colourists in the early 20th century. Accompanied by extensive editorial commentary, this collection will be of great interest to students of Art History and Scottish History.